Belugas (Delphinapterus leucas) create facial displays during social interactions by changing the shape of their melons - Justin T. Richard; Isabelle Pellegrini; Rachael Levine (Animal Cognition)
Abstract Beluga whales are considered unique among odontocetes in their ability to visibly alter the appearance of their head by changing the shape of the melon, but only anecdotal observations are available to evaluate the use or potential function of these melon shapes. This study of belugas in professionally managed care aimed to establish an ethogram for the repertoire of categorizable melon shapes and then evaluate their potential function as intentional communication signals by determining if they were produced and elaborated during social interactions of varying behavioral contexts while in the line of sight of a recipient. Five different melon shapes were reliably identified in video observations of the primary study population (n = 4) and externally validated in a second aquarium population (n = 51). Among the 2570 melon shapes observed from the primary study subjects, melon shapes occurred 34 × more frequently during social interactions (1.72 per minute) than outside of social interactions (0.05 per minute). Melon shapes occurring during social interactions were performed within the line of sight of a recipient 93.6% of the time. The frequency of occurrence of the different melon shapes varied across behavioral contexts. Elaboration of melon shapes through extended duration and the occurrence of concurrent open mouth displays varied by shape type and across behavioral contexts. Melon shapes seem to function as visual displays, with some characteristics of intentional communication. This ability could yield adaptive benefits to belugas, given their complex social structure and hypothesized mating system that emphasizes pre-copulatory female mate choice.